Essays in Development Economics: Intrahousehold Decision Making in Developing Countries - Puthenmadathil Jose, Anu (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2023)
Providing insights into mechanisms through which households manage resources, this thesis aims to add to the empirical evidence on strategic decision-making among spouses using experimental and survey data. While the chapters make important contributions to our understanding of mechanisms of household deliberations, the findings are relevant for policymakers and practitioners interested in improving welfare through interventions in social protection and financial inclusion. Chapter 1 focuses on the comparative effectiveness of strategies and delivery mechanisms used in the development policy sphere for women empowerment. To understand interactions between mental accounting, spousal control and couple's communication, informed by recent innovations in the fin-tech space, we mimicked practical iterations of income type and spousal monitoring in a pre-registered lab-in-the-field experiment with 1,008 couples in Kolkata, India. The experimental design was a cross randomisation where, first, for half the sample, the female spouse worked for resources, and the other half received money as a gift before allocation decisions were made under five different monitoring frameworks that mirror potential iterations in account type: private, private labelled, visible, approval and negotiation. Our findings highlight the importance of female labour market participation and the mental accounting of earned resources. Earned income by wives was allocated to a greater extent to accounts over which she had more control. While no overall effect of workfare on consumption decisions was found, we did find that for women who have low control over money, earning money induces them to spend more on their personal consumption. Labelling newly acquired resources for household purposes in individual accounts for both wife and husband did not alter expenditure patterns, indicating a failure of the mental accounting of household resources in individual accounts. Spousal visibility of male decision-making ensures they allocate more towards the collective and away from themselves. Conversely, spousal transparency and communication did not alter the wife's allocation patterns, but such innovations came at a cost for the less empowered: in households where the wife has low control over money or is more risk averse, the visibility of her decisions by the husband or an approval requirement from her husband for her decisions leads her to allocate more to accounts he has control in. Our findings provide important insights for the design and delivery of social protection programmes and suggest the existence of potential welfare gains of shared or joint financial products for managing household resources. With a focus on economic autonomy and economic violence, chapter 2 aims to understand how exogenous changes in male perspectives through a male-focused gender transformative program in the Democratic Republic of Congo (DRC) affect economic violence experienced by their partner for different levels of spousal discordance on wife's economic autonomy. This study attempts to uncover the relationship between women’s empowerment and intimate partner violence that various theoretical channels and mixed empirical findings have previously characterised. First, pre-intervention, we find that households where women take economic autonomy when their husbands do not acknowledge her autonomy are associated with more economic violence. Second, we find that male-focused gender-transformative programs are most effective in households with higher levels of spousal economic contest and violence. In contrast, the intervention had no significant effect on economic violence in households where women did not contest for autonomy. While previous studies have focused on how women’s self-reported bargaining power can influence the effects of female empowerment programs, this chapter is the first work to take into account the implications of differences in spouses’ views of autonomy for the success of such programs. Chapter 3 examines how income shocks affect intrahousehold expenditure patterns in agricultural economies. Using rainfall data and household panel data, with responses from both spouses, from rural Ethiopia, we show that a negative household level income shock significantly reduces female expenditures relative to male expenditures (31.4% greater reduction). We specifically explore the channel of female and male labour supply as an explanation behind the observed differentiated impacts on spousal consumption. We find evidence that engaging in off-farm employment provides women with an independent income and allows them to smooth their expenditures during farm income shock. We also find evidence that the wife's involvement in managing and controlling the household farm, measured as her time spent on the farm relative to the husband, negates the shock-induced gender differential in expenditures. Together, these results highlight gender-specific impacts of household income shocks on consumption and the role female economic opportunities play in negating intrahousehold impacts of such household shocks.
APPROVED
Keywords: development economics; intrahousehold decision making